2017
DOI: 10.4081/aiol.2017.6429
|View full text |Cite
|
Sign up to set email alerts
|

Toxic cyanobacteria and cyanotoxins in European waters – recent progress achieved through the CYANOCOST Action and challenges for further research

Abstract: This review aims to summarise the outcomes of some recent European research concerning toxic cyanobacteria and cyanotoxins, with an emphasis on developments within the framework of the CYANOCOST Action: COST Action ES1105, Cyanobacterial Blooms and Toxins in Water Resources: Occurrence, Impacts and Management. Highlights of the Action include phycological and ecological studies, development of advanced techniques for cyanotoxin analysis, elucidation of cyanotoxin modes of action, management techniques to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 127 publications
(146 reference statements)
1
42
0
7
Order By: Relevance
“…Regarding to MC‐LR, there are several studies in the scientific literature in HepG2 cells but most of them used lower concentrations than in the present work as they were focused on the study of toxicity mechanisms and not in deriving EC 50 values (ie, Refs. ). Chong et al concluded that MC‐LR did not cause cytotoxic effects in HepG2 cells and other hepatic cell line in 48–96 h of exposure to concentrations up to 100 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding to MC‐LR, there are several studies in the scientific literature in HepG2 cells but most of them used lower concentrations than in the present work as they were focused on the study of toxicity mechanisms and not in deriving EC 50 values (ie, Refs. ). Chong et al concluded that MC‐LR did not cause cytotoxic effects in HepG2 cells and other hepatic cell line in 48–96 h of exposure to concentrations up to 100 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
“…Also, Sabart et al, reported that the concentration of each cyanotoxin changes spatially and temporally during a bloom. In Europe, Meriluoto et al also evidenced the occurrence of cyanobacteria and cyanotoxins, highlighting CYN as a toxin of growing importance in European waters and elsewhere. Other authors have also reported the simultaneous occurrence of different cyanobacterial toxins, although up to date the number of studies are still very scarce .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the appearance or reappearance of potentially invasive alien species due to poorly managed introductions and fish restocking, and the increasingly frequent appearance or spread of toxic or harmful species (e.g, dangerous algal blooms, jellyfish), as a result of physical, chemical and ecological alterations of terrestrial and marine water bodies, have become themes of strong scientific and socio-economic interest (Boero et al, 2016;Hamilton et al, 2014;Meriluoto et al, 2017a;Wells and Bengt, 2018). This was confirmed by our survey's answers.…”
Section: Cluster 1 Where Are Aquatic Sciences Today?mentioning
confidence: 99%
“…Similarly to other toxic cyanobacteria, P. rubescens produces several microcystin (MC) congeners, most of them highly toxic for animals and humans (Meriluoto et al, 2017;Metcalf and Codd, 2012). The formation of cyanobacterial blooms in waters used for drinking purposes has been associated to the occurrence of human cancer in a number of countries (Fleming et al, 2002;Svircev et al, 2009;Ueno et al, 1996;Zhou et al, 2002).…”
Section: Vertical and Horizontal Distribution Of The Microcystin Prodmentioning
confidence: 99%